Belanja Jasa Konsultansi Penyusunan Kajian Pemetaan Daya Saing Daerah Kota Surakarta Tahun 2023 - Viriani Noviasari Dewi; Budi Purwanto (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2023)
The scope of competitiveness at the regional level includes various benchmark factors including economic growth and stability factors, regional convergence and divergence, diversity, and the impact of regional situations (Chrobocińska, 2021). The broad scope of regional competitiveness can then be interpreted broadly to mean that competitiveness is closely related to regional development and the stimuli that accompany it, so that competitiveness factors drive regional development factors and vice versa. Moreover, several literatures use this competitiveness as a marker of sustainability (competitiveness index as evidence of sustainability) for a geographic scope including cities, districts, provinces and countries (Judrupa, 2021; Korauš, Havierniková, Gombár, Černák, & Felcan, 2020 ; Nogueira & Madaleno, 2023). This strong connectivity between competitiveness, development and the sustainability paradigm was then used as one of the foundations for the implementation of the Sustainable Regional Competitiveness Index by the National Research and Innovation Agency (BRIN) of the Republic of Indonesia.